Characterization and Evaluation of Wild Annual Cicer Species for Agro‐morphological Traits and Major Biotic Stresses under Northwestern Indian Conditions. Issue 1 (1st January 2014) - Singh, Mohar; Bisht, Ishwari Singh; Dutta, Manoranjan; Kumar, Krishna; Basandrai, Ashwani Kumar; Kaur, Lavinder; Sirari, Asmita; Khan, Z.; Rizvi, Aqeel Hasan; Sarker, Ashutosh; Bansal, Kailash Chander
ABSTRACT: Systematic characterization and evaluation of the wild gene pool for breeding purposes is a common practice in an increasing number of cultivated crop species. Substantial yield improvement of cultivated chickpea ( Cicer arietinum L.) has been limited by the loss of useful genes for higher yield and lack of resistance to major biotic stresses. In the present study, a total of 88 wild accessions of six annual Cicer species viz., C. reticulatum Ladizinsky, C. echinospermum P.H. Davis, C. judaicum Boiss., C. pinnatifidum Jarb. & Spach, C. bijugum Rech. f., and C. yamashitae Kitam., along with three check varieties (controls) of cultivated chickpea namely, Pusa 256, Pusa 1103, and JG 11, were characterized and evaluated for phenological and agro‐morphological traits, including their reaction to the major fungal diseases [Ascochyta blight caused by Ascochyta rabiei (Pass.) Labr. and Botrytis gray mold caused by Botrytis cinerea Pers. ex. Fr.] and root knot nematode ( Meliodogyne incognita ). Wild Cicer accessions exhibited variation for some morphological traits, including plant pigmentation in C. reticulatum, C. judaicum, and C. pinnatifidum ; number of leaflets leaf −1 in C. reticulatum, C. echinospermum, C. judaicum, C. pinnatifidum, and C. bijugum ; and seed color in C. reticulatum, C. judaicum, and C. pinnatifidum . Likewise, variation for agro‐morphological traits was also studied, that is, earliness, number of branches plant −1, and number of pods plant −1, etc. Some of these were comparable with the cultivated genotypes. Pattern of within‐species diversity was also estimated using Ward's Minimum Variance Dendrogram and principal components analysis for important agro‐morphological traits. Among the wild Cicer species, C. judaicum and C. pinnatifidum had the greatest number of resistant accessions including multiple resistance for Ascochyta blight, Botrytis gray mold, and root knot nematode. Variability among wild annual Cicer accessions is invaluable and can be exploited following introgression into cultivated chickpea. It will also help in the flow of useful genes from the wild to the cultivated gene pool and generating additional variation for use in chickpea improvement.